2022
DOI: 10.3389/fcell.2022.745883
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Arabidopsis Protein Kinases That Harbor Functional Type 1 Peroxisomal Targeting Signals

Abstract: Peroxisomes are eukaryotic specific organelles that perform diverse metabolic functions including fatty acid β-oxidation, reactive species metabolism, photorespiration, and responses to stress. However, the potential regulation of these functions by post-translational modifications, including protein phosphorylation, has had limited study. Recently, we identified and catalogued a large number of peroxisomal phosphorylated proteins, implicating the presence of protein kinases in this organelle. Here, we employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Several proteins from A. thaliana show a dual localization to peroxisomes and to other compartments, often due to PTS1 motifs with low import efficiency ( Reumann et al, 2007 ; Kataya and Reumann, 2010 ; Lingner et al, 2011 ). Interestingly, protein kinases were identified that often contain unusual but functional PTS1 motifs ( Kataya et al, 2022 ). These findings are of particular interest as little is known about the phosphorylation-dependent regulation of enzymes inside of the peroxisomal lumen.…”
Section: Dually Targeted Proteins—the Dark Matter Of the Peroxisomal ...mentioning
confidence: 99%
“…Several proteins from A. thaliana show a dual localization to peroxisomes and to other compartments, often due to PTS1 motifs with low import efficiency ( Reumann et al, 2007 ; Kataya and Reumann, 2010 ; Lingner et al, 2011 ). Interestingly, protein kinases were identified that often contain unusual but functional PTS1 motifs ( Kataya et al, 2022 ). These findings are of particular interest as little is known about the phosphorylation-dependent regulation of enzymes inside of the peroxisomal lumen.…”
Section: Dually Targeted Proteins—the Dark Matter Of the Peroxisomal ...mentioning
confidence: 99%